Bei Schmerzen im Bereich der Harnwege gilt: Erst den Schmerz lokalisieren, dann gezielt behandeln = Pelvic pain--definitions, diagnosis and therapeutic options - Bross, Stephan; Alken, Peter (MMW - Fortschritte der Medizin, 2004)
Depending on the location, bladder, urethral, penile and prostate pain syndromes are distinguished. In addition to the investigation of urine and ejaculate with the aim of detecting an infection, clinical examination, uroflowmetry are employed and, where indicated, imaging techniques to exclude cancer disease. Chronic pelvic pain is a non-cancer-related pain persisting for more than six months. In the absence of an underlying treatable disease, appropriate pain therapy can be initiated with antiphlogistic analgesics, COX 2 inhibitors or opioids. Depending on the clinical presentation, further therapeutic options or such non-drug measures as bladder training, dietetic measures or surgery may be applied in addition.